The Relationship Between Lower Limb Biomechanics and Muscle Strength With Non-Specific Low Back Pain - Kotryna Žaltauskaitė; Vilma Juodžbalienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. The rising incidence of low back pain (LBP) poses a challenge in terms of pain-related healthcare costs and reduced work capacity. The main researched causes of LBP are such sociocultural and demographic aspects as sedentary work and age. Changes in body and step biomechanics have been found to be involved in the onset of LBP as well. However, analysis of lower limb biomechanics and muscle strength in relation to non-specific low back pain (NSLBP) is insufficient, thus the present study aims to explore this topic from a biomechanical and muscle strength perspective.